Distributed Leadership: Teachers’ and Principals’ Perceptions Match and the Association With Teacher Work Satisfaction and Autonomy - Peter D. Wiens; Vanessa Vongkulluksn; Hui-Ling Wendy Pan (AERA Open)
Schools where principals and teachers collaborate to develop a culture of distributed leadership provide the best environments for teaching and learning. However, the alignment between principals’ and teachers’ perceptions of distributed leadership and association with teacher outcomes requires further investigation. Using TALIS 2018 data, this study explored how the (mis)match of principal and teacher perceptions of distributed leadership may be associated with levels of teacher work satisfaction and teacher autonomy. Hierarchical linear modeling and polynomial regression with response surface analysis were employed for data analysis. Findings indicate that principals and teachers had different views on distributed leadership, and these differences were associated with levels of teacher autonomy. When principals overestimated distributed leadership compared to teachers, teacher autonomy declined. Moreover, teachers’ perceptions of distributed leadership were the strongest predictors of work satisfaction. These findings highlight the importance of understanding perceptual gaps between principals and teachers to develop leadership strategies.